Censuses of Anatidae in the central delta of the Niger and the Senegal delta---January 1972 - Roux, Francis (Wildfowl, 1973)
The central delta of the Niger was surveyed by air between 3 and 5 January 1972 and the Senegal delta from 14 to 18 January 1972. Details of the hydrological conditions are given. Attention was concentrated on the Anatidae, particularly those of Palaearctic origin. Useful information was also gained on many other types of waterfowl. Detailed lists of the birds counted are provided, together with assessments of their relative importance and the environmental features affecting their distribution.